Sárga csillagos kocsmák - Konkol, Mate (Hungary, 2014)
Conversations in Budapest pubs located in houses which in 1944 were marked with the yellow Star of David. In the summer of 1944, during the final months of Miklós Horthy’s governorship, Hungarian political leaders decided that Budapest Jews were to be forcibly expelled from their homes. On June 16, the mayor of Budapest issued a decree that marked out almost 2,000 apartment buildings in the city, into which 220,000 targeted individuals were obliged to move: 187,000 Jews and a further 35,000 converted Jews, subjected to a series of “Jewish laws”, and forced to wear a yellow Star of David on their clothing. The houses served the same purpose as the ghetto, a preparatory stage for deportation. Today, most of the so called “yellow star” houses still stand in Budapest and a number of them are pubs and clubs. Does it matter to the pub-goers today?
Film also on HDD Verzio11/12 located: M22 R17 S2 R4
Verzio Film Festival Submission
Keywords: Documentary films